Profile of Some Trace Elements in the Liver of Camels, Sheep, and Goats in the Sudan. (7th December 2013) - Ibrahim, Ibrahim Abdullah; Shamat, Ali Mahmoud; Hussien, Mohammed Osman; El Hussein, Abdel Rahim Mohammed
Abstract : One hundred camels ( Camelus dromedaries ) and fifty sheep and goats being adult, male, and apparently healthy field animals were studied to provide data regarding the normal values of some hepatic trace elements. Liver samples were collected during postmortem examination, digested, and analyzed for Cu, Zn, Fe, Co, and Mn using atomic absorption spectrophotometry. The results showed that the differences in mean liver concentrations of Cu, Zn, Fe, and Co between camels, sheep, and goats were statistically significant (P < 0.05 ). Hepatic Cu, Fe, and Co concentrations were higher in camels than in sheep and goats. All liver samples were adequate for Fe and Co, whereas only camel liver was adequate for Cu. In camels, hepatic Zn concentration was inadequately lower than that in sheep and goats. No difference in Mn concentration was detected between camels, sheep, and goats. All liver samples were inadequate compared to free-ranging herbivores. In camels, significant correlation (r 2 = - 0.207, P value = 0.04) was detected between Zn and Co, whereas in sheep significant correlation (r 2 = - 0.444, P value = 0.026) was detected between Zn and Mn. No significant correlation between trace elements was detected in goats.